Does scale matter? The costs of HIV-prevention interventions for commercial sex workers in India - Lorna Guinness; Lilani Kumaranayake; Bhuvaneswari Rajaraman; Girija Sankaranarayanan; Gangadhar Vannela; P. Raghupathi; Alex George
OBJECTIVE: To explore how the scale of a project affects both the total costs and average costs of HIV prevention in India. METHODS: Economic cost data and measures of scale (coverage and service volume indicators for number of cases of sexually transmitted infections (STIs) referred, number of STIs treated, condoms distributed and contacts made with target groups) were collected from 17 interventions run by nongovernmental organizations aimed at commercial sex workers in southern India. Nonparametric methods and regression analyses were used to look at the relationship between total costs, unit costs and scale. FINDINGS: Coverage varied from 250 to 2008 sex workers. Annual costs ranged from US$ 11 274 to US$ 52 793. The median cost per sex worker reached was US$ 19.21 (range = US$ 10.00-51.00). The scale variables explain more than 50% of the variation in unit costs for all of the unit cost measures except cost per contact. Total costs and unit costs have non-linear relationships to scale. CONCLUSION: Average costs vary with the scale of the project. Estimates of resource requirements based on a constant average cost could underestimate or overestimate total costs. The results highlight the importance of improving scale-specific cost information for planning.